2022
DOI: 10.1111/ene.15324
|View full text |Cite
|
Sign up to set email alerts
|

One‐year cognitive follow‐up of COVID‐19 hospitalized patients

Abstract: Background and purpose Cognitive dysfunction has been observed following recovery from COVID‐19. To the best of our knowledge, however, no study has assessed the progression of cognitive impairment after 1 year. The aim was to assess cognitive functioning at 1 year from hospital discharge, and eventual associations with specific clinical variables. Methods Seventy‐six patients (aged 22–74 years) who had been hospitalized for COVID‐19 were recruited. Patients received ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
56
5
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 47 publications
(89 reference statements)
17
56
5
4
Order By: Relevance
“…This is in line with results found in previous studies, revealing the association of olfactory and cognitive abilities in post COVID-19 patients [ 29 , 71 , 72 ]. In addition, it was also suggested that the more COVID-19 symptoms were more severe and persistent, such as olfactory impairment, the more cognitive impairment was higher [ 29 , 62 , 72 ]. Our results support this observation: the higher were TODA threshold scores, revealing deteriorated olfactory perception, the lower were PPTT scores.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with results found in previous studies, revealing the association of olfactory and cognitive abilities in post COVID-19 patients [ 29 , 71 , 72 ]. In addition, it was also suggested that the more COVID-19 symptoms were more severe and persistent, such as olfactory impairment, the more cognitive impairment was higher [ 29 , 62 , 72 ]. Our results support this observation: the higher were TODA threshold scores, revealing deteriorated olfactory perception, the lower were PPTT scores.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with a recent study revealing a tissue-contrast reduction in the orbitofrontal cortex [ 26 ] which is one of the brain areas governing attentional abilities. The fact that generative naming time and T-TODA scores were correlated is in accordance with studies [ 32 , 72 ] that showed olfactory disorders are associated with attentional, memory and executive function disorders. This result is also in line with studies [ 62 , 72 ] suggesting that the severity and persistence of COVID-19 neurological symptoms influence cognitive impairment extent.…”
Section: Discussionsupporting
confidence: 90%
“…However, in current clinical practice, it is very difficult to understand and define the “type and severity of the self-reported cognitive deficits”, such as brain fog and difficulty concentrating, and consequently to more objectively measure cognitive performance. Indeed, most studies focused on the prevalence of cognitive alterations due to Long COVID, but not on the psychometric tools to measure the cognitive domains affected by the post-SARS-CoV-2 infection [ 44 ]. To overcome this issue, Alemanno et al measured the cognitive abilities of patients in the COVID-19 post-acute phase that had experienced severe disease, using the Montreal Cognitive Assessment (MoCA).…”
Section: Cognitive Dysfunctions Psychiatric Symptoms and Behavioral A...mentioning
confidence: 99%
“…Overall, despite methodological differences - e.g., telephone vs. in-person assessment, screening vs. second-level assessment [ 14 , 15 ] – converging evidence shows that cognitive deficits in COVID-19 patients can be appreciated from the early sub-acute stage [ 16 ] and few days after hospital discharge [ [17] , [18] , [19] ], up to 5–7 months [ 14 , [20] , [21] , [22] ] and even 1 year after hospital discharge [ 23 , 24 ]. A recent review by Crivelli and colleagues [ 14 ] on 27 studies including 2049 individuals, highlights a broad spectrum of cognitive impairments mostly involving executive functions, attention and long-term memory (i.e., the ability to learn new information and/or recall it at a later time).…”
Section: Introductionmentioning
confidence: 99%